INTERAKSI DENGAN CUCU, KUALITAS PERKEMBANGAN, DAN GEJALA STRES PADA KAKEK/NENEK - Herawati, Puspita; Krisnatuti, Diah; Alfiasari, Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2013)
This research aimed to analyze intergenerational interaction between grandparents and grandchildren, quality of grandparent’s development, symptoms of grandparent’s stress, and also its correlation among those variables. This research located at one of village in Rembang District, Central Java Province and involved 30 grandfathers and 30 grandmothers with their grandchildren that choosen by snowball method. Data was collected by interview using structure questionnaire. Data was analyzed by descriptive analysis, independent t-test, and correlation analysis. Quality of development (cognitive and reflective dimension) of grandfathers were higher than grandmothers. Interaction type of formal, fun-seeking, and distant figure were statistically different between grandfathers and grandmothers. Grandparent’s education was correlated positively significant with type of formal and fun-seeking. Father and mother age of grandchildren was correlated positively significant with type of distant figure. Grandparent’s income per capita was correlated negatively significant with psychological symptoms of stress and general symptoms of stress. Interaction role of remote was correlated negatively with physical symptoms of stress and general symptoms of stress.